The effect of binahong leaf extract on hair growth and histopathological examination of skin tissue in wound healing - Himmawan, Arif; Bangun, Andreas Xaverio; Dewi, N.R.S. Vissy Puspa (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Binahong leaves are often used as traditional medicine to cure wounds, rheumatism, gout, lack of appetite, nosebleeds, kidney inflammation, intestinal inflammation, and cancer. And not many people know that binahong leaves can also accelerate the growth of hair follicles, therefore this study was conducted, namely to analyze and test the effect of giving binahong leaf extract (Anderera cardifolia) in collagenization to accelerate the healing process of incision wounds on the back of white rats (Rattus norvegicus) wistar strain and see the histopathological picture on rat skin tissue. This study used 24 male rats (Rattus norvegicus) wistar strains as samples, then divided into 4 groups with each group of 6 rats, and treated for 14 days. for 14 days On the last day the hair length of the control group/P0 was 0.45 and became the lowest group in hair growth in this treatment, while in the treatment of groups PI, P2 and P3 it was known that the P3 group experienced the fastest hair follicle extension with a result of 1.24 cm. This is also in line with the results of hispatology images for the treatment of treatment group 3 (P3) which is the fastest group of incision wound healing in skin tissue because based on these observations the skin epithelial tissue is seen to begin to thicken and almost perfect.